DEVELOPMENT AND CYTOCHEMICAL STUDIES OF EMBRYO SAC, EMBRYO AND ENDOSPERM IN ALLIUM PERONINIANUM - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2010)
The development of the embryo in Allium peroninianum Aznav., is of the Onagrad type. The developmental stages include the followings: Proembryo, globular embryo, spheroidal, stick-shaped and cylindrical mature embryo. The endosperm of A. peronnianum follows nuclear type of development. The endosperm becomes completely cellular at the stage of globular embryo. The chalazal end of the embryo sac forms a coenocytic haustorium. The nuclei in haustorium are hypertrophic. However, some features of endosperm development show striking differences from the nuclear type. The embryo sac is divided into two chambers at free nuclear stage: small micropylar and large chalazal chambers. Both the chambers are firstly free nuclear, later they become cellular. Cytochemical tests indicate the presence of higher amounts of insoluble and acidic polysaccharides in haustorium than that of endosperm but there were no lipids in both.
Keywords: CEPA L.; GYNOGENESIS; TUBEROSUM